Edição de fotografia no jornal Zero Hora: entre a produção, a recepção e o produto - Moraes, Cybeli Almeida (Universidade do Vale do Rio do Sinos, 2007)
The present essay intends to discuss the photography edition of the Zero Hora daily newspaper, approaching the production, the reception and the photojournalistic product as the three instances that allow us to understand this process. Starting from a quanti-qualitative study on the photography in the media printed - and also of the contributions around the sense processes, the journalism theories and the audiovisual studies -, the present research intends to identify the “definer elements” of the nature and logics of the use of the photography in Zero Hora, being structured around the “critic” of the image accomplished in the box Foto comentada. Starting from this tensive space among photography, photographic edition, reader and newspaper, intends to notice for which directions, in the extent of the photojournalistic system, these discussions appear. Among the accomplished methodological movements, are the incursions in the reception and production fields (through interviews, participant observation and observation of the box Foto comentada), and also the analysis of 172 photographs published in Zero Hora during the year of 2005. As main theoretical contributions, we can mention authors Jorge Pedro Sousa, Susan Sontag, Donis A. Dondis, Nélson Traquina, Mauro Wolf, Roland Barthes, Vilém Flusser, Pepe Baeza, Henri Bergson, Suzana Kilpp and José Luiz Braga, among others.
Keywords: edição; fotografia; fotógrafo; imagem; Zero Hora; fotojornalismo; journalism; photography; photojournalism; edition; Ciências Sociais Aplicadas